School discipline management : legal restrictions and the importance of legal literacy amongst discipline teachers - Syed Muhamad Ubaidillah, Syed Husin (2021)
Today, parents and pupils are more aware of their rights. Such a trend could lead to the increasing number of litigation in education. As school law enforcers, teachers face legal restrictions which spell out certain limits to them in discharging their duties in discipline management. In order to perform their duties effectively, they have to ignore the restrictions and bear the risks individually. Ignorance of law too, has resulted in teachers to overlook some relevant legal provisions in the preparation of rules and documents pertaining to school discipline. They received no legal training in their pre-service program and they are legally illiterate. An awareness and understanding of the law, therefore, is part of the professional knowledge required for them. They should understand educational law so that they can both protect their rights and ensure the safety of young people. This research was aimed to gauge the level of legal literacy among discipline teachers in Malaysia and their knowledge in the management of school discipline and to examine whether the existing or present rules and regulations/law become restrictions to them in managing pupils’ discipline Mixed model was used to carry out this research. The research instrument used for the qualitative data collection procedure was the interview protocol and questionnaire for quantitative data. This study involved 161 discipline teachers from 23 schools and 3 principals from 3 different schools in the Kuantan district. From the analysis, the results were found to be confirming to each other or converging in the same direction, thereby permitting a strong conclusion to be drawn regarding the issues discussed in this research. The findings from inferential analysis discovered that there were significant relationship between the level of discipline teachers’ knowledge in law and the management of school discipline with 0.317 correlation at 0.01 two-tailed which means better legal knowledge may contribute to better management of school discipline. The results in the qualitative analysis too, showed they were corresponding with the quantitative analysis. The mean score (3.395) for teachers’ knowledge in law related to education showed that teachers had moderate level of legal knowledge. Therefore, the findings from this study support the propositions that school teachers are lack of legal knowledge and they encounter many restrictions in managing school discipline. The research is hoped to contribute towards widening teachers’ knowledge in the area of school laws and better management of school discipline.